Microfluidic‐assisted preparation of nano and microscale chitosan based 3D composite materials: Comparison with conventional methods. Issue 40 (2nd August 2022) - Kimna, Ceren; Deger, Sibel; Tamburaci, Sedef; Tihminlioglu, Funda
Abstract: Although nanofillers contribute to improved physical characteristics and biological functionalities of polymer‐based biomaterials, their dispersion in polymer matrices is still a challenging issue in terms of obtaining consistency for the inherent properties. To tackle this problem, homogenization techniques are applied to disperse the nanofillers in such polymers, however, these methods can cause undesired changes especially in the rheological properties and the physical structure of the biopolymer matrices. Recently, as a novel homogenization technique, microfluidization has been used to homogenize polymer nanocomposites to minimize these limitations. In this study, two different nanocomposite structures as chitosan/montmorillonite (CS/MMT) and chitosan/polyhedral oligomeric silsesquioxane nanocages (CS/POSS) were homogenized with microfluidization and investigated in terms of physical alterations. Furthermore, the effect of microfluidizer technique on material characteristics was compared with conventional homogenization techniques, i.e., ultrasonic bath and sonication in terms of solution, nano – (e.g., hydrodynamic size, drug encapsulation) and macroscopic material characteristics (e.g., porosity, mechanical properties, swelling and thermal degradation). It was found that the microfluidizer homogenization improves the physical characteristics in both nano and macroscale materials: Nanospheres obtained from CS/MMT composites showed enhanced stability, uniform size distribution (<100 nm, PDI: <0.2), and good encapsulation efficiency (>50%) whereas 3D porous CS/POSS scaffolds showed improved structural uniformity (i.e., homogeneous and interconnected microstructure) and enhanced thermal and mechanical properties. The obtained results indicate that the microfluidizer homogenization ensures a successful nanofiller dispersion in polymer matrices, thereby improving the biomaterial characteristics impressively compared to the sonication methods. Abstract :